PENGARUH BRAND AWARENESS, PERSONAL SELLING DAN PERIKLANAN TERHADAP KEPUTUSAN PEMBELIAN PELANGGAN PT. SEMESTANUSTRA DISTRINDO - Michelle, Michelle; Fitriano, Andre; Chandra, Herman; Nasution, Ismail (Mount Hope Management International Journal, 2025)
The purpose of this study is to analyze PT Semestanustra Distrindo's marketing data to identify the factors that impact customer choice in relation to advertising, personal selling, and brand recognition. Customers of PT Semestanustra Distrindo, the precise count of whom is not known, make up the population under study. Surveys were sent out to gather data, which was then processed and evaluated using SPSS 21. Results from hypothesis testing reveal that brand awareness, personal selling, and advertising are the three independent variables at PT Semestanustra Distrindo that influence purchase choices, proving that variable 1). A favorable and statistically significant relationship exists between brand awareness and purchase behavior, 2). Personal selling influences consumers' choices to buy in a favorable and statistically significant way, 3. There is a positive and statistically significant relationship between advertising and consumer spending (4). Decisions to buy at PT Semestanustra Distrindo are impacted by advertising, personal selling, and brand recognition all at once. Brand awareness, personal selling, and advertising impact purchase choices at PT Semestanustra Distrindo by 51.7%, according to the coefficient of determination. The remaining 48.3% is influenced by other factors that were not explored in this study. At 39.1%, personal selling is the most influential component when it comes to purchase choices.